Women empowerment through local wisdom as production differentiation strategy - Yeyen Komalasari; Eka Putri Suryantari; Tjokorda Bagus Putra Marhaendra (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This article explores the application of production differentiation strategy by women empowerment through local wisdom of Nasi Koco in the herritage area, Gajah Mada Street, Denpasar-Bali. The purpose of this article is to increase the sales of Nasi Koco by implementing new strategies to win the competition in similar businesses that have sprung up. The strategy that can be offered is a product differentiation, so that the product is more varied and not monotonous, that attracts consumer interest. The product differentiation strategy offered refers more to women's empowerment through local wisdom, namely making products or food variations needed for ceremonies, where as we know people's lives in Bali are full of a series of religious ceremonies. The study employed qualitative approaches using narrative research by observation, interview, and documentation. The result of the study base on an in-depth interview with Balinese women who understand Balinese traditional culture, the advice that can be given is to make product variations, not just Nasi Jinggo or Nasi Wrap as usual, but to make it more varied. Suggested variations are Nasi Tumpeng, Nasi Yasa, and Nasi Kelangi, which are usually used for traditional activities in Bali.